Synthesis, characterization and thermal properties of chalcone methacrylamide polymers containing methoxy group in side chain - Solmaz, Adnan; Ilter, Zulfiye; Kaya, Ismet (Springer, 2021)
In this study, thermal and dielectric properties of chalcone methacrylamide polymers containing methoxy group in side chain were studied. At first the chalcone compounds abbreviated as CHAL1, CHAL2, and CHAL3 containing the methoxy group in the side chain were synthesized. Then, the monomers abbreviated as M1, M2 and M3 were synthesized by the reaction of chalcone compounds with methacryloylchloride. The chalcone methacrylamide polymers abbreviated as P1, P2 and P3 were prepared via the free radical polymerization at 70 C-o in DMF solution. The structures of synthesized chalcone compounds were characterized by FT-IR, UV-Vis, H-1 and (13) C-NMR. Thermal behavior of polymers was investigated with DSC and TGA measurements. The glass transition temperatures (T-g) of P1, P2 and P3 were found at 85, 95 and 140 C-o, respectively, from DSC measurements. According to the Flynn-Wall-Ozawa (FWO) method, the average decomposition activation energy of the P2 was calculated to be 113.60 kJ mol(- 1) by TGA curves at different heating rates such as 5, 10, 15 and 20 C-o min(- 1). For investigating the dielectric properties of polymers, dielectric constant (epsilon'), dielectric loss factor (epsilon), and ac conductivity values were measured using an impedance analyzer in the frequency range of 100 Hz-10 kHz frequencies. The results were plotted as a function of frequency. The conductivity values of P1, P2 and P3 were found to be 1.74, 2.24 and 2.63 x 10(- 9) S cm(- 1), respectively. The surface morphologies of the polymers were examined by SEM. The optical properties of polymers were examined by UV-Vis. The biological activities of polymers were determined by disk diffusion method. Polymers have exhibited good antimicrobial property against Staphylococcus aureus, Klebsiella pneumonia and have exhibited good antifungal property against Candida albicans.
Keywords: Free Radical Polymerization; Chalcone; Thermal Properties; Dielectric Features; Biological Activity